Strategic sourcing: Developing a progressive framework for make-or-buy decisions - Rubén Medina-Serrano; Reyes González-Ramírez; José Gascó; Juan Llopis (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: Make-or-buy decisions represent a critical dilemma faced by many firms. The appropriate decision between designing and manufacturing parts or services in-house, buying them from external providers or combining both is a fundamental firm process. This paper seeks to address this question by updating the traditional make-or-buy literature with new academic insights, developing a make-or-buy framework with a tool for its operationalisation to help managers evaluate sourcing decisions. Design/methodology/approach: First, a literature review of the principal theories and approaches about make-or-buy decisions is discussed. Second, the development of the make-or-buy framework is described and explained based on the results of qualitative interviews with practitioners and a set of interviews of an in-firm case study. Third, the results and the implementation of the framework are outlined. Findings: Our study not only validates the proposed framework through a set of in-firm make-or-buy decisions, but also provides a structure for its implementation and design a decision matrix with a pairwise comparison tool for helping practitioners to put the framework into practice. Research limitations/implications: This paper aims to contribute to the study of the make-or-buy literature in supply chain management through the graphical representation of why and how make-or-buy decisions are made. Interestingly, the paper presents relevant dimensions and factors to be studied and evaluates possible outcomes when approaching make-or-buy decisions. Originality/value: Our results suggest that practitioners should combine this framework with a pairwise comparison matrix and a multi-criteria decision analysis based on the TOPSIS methodology to assess strategic sourcing decisions.
Keywords: 650; make-or-buy decisions; decision-making; outsourcing; plural sourcing; hybrid sourcing; literature review